2016
DOI: 10.1007/s12402-016-0204-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of sleep quality and quantity in moderating the effectiveness of medication in the treatment of children with ADHD

Abstract: The current study examined: (1) whether long-acting stimulant medication is effective in improving performance on measures of memory, attention, and academic productivity; and (2) whether sleep impacts the relationship between medication and performance. Participants were 21 newly diagnosed, medication-naïve children (mean age = 9.1 years) with ADHD, who participated in a 4-week blinded placebo-controlled randomized trial of long-acting MPH. Participants underwent assessments of sleep (i.e., polysomnography) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It is unclear to what degree sleep and circadian rhythm disturbances in ADHD constitute epiphenomena of the disorder, or might be moderated/mediated by stimulant medications which are the mainstay of treatment (Ironside et al, 2010;Morash-Conway et al, 2017). Studies in at-risk groups absent of psychiatric diagnosis can enable an investigation of sleep and circadian functioning shed of these confounds.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear to what degree sleep and circadian rhythm disturbances in ADHD constitute epiphenomena of the disorder, or might be moderated/mediated by stimulant medications which are the mainstay of treatment (Ironside et al, 2010;Morash-Conway et al, 2017). Studies in at-risk groups absent of psychiatric diagnosis can enable an investigation of sleep and circadian functioning shed of these confounds.…”
Section: Introductionmentioning
confidence: 99%
“…Morash-Conway and colleagues (2016) also examined the impact of long-acting MPH on school-age children with ADHD, with sleep measured by overnight PSG. In this study, total sleep time was decreased by 40 minutes on MPH compared to placebo (Morash-Conway et al, 2016). However, they also found that children who were considered "good sleepers" prior to medication were more likely to have improvements in attention accuracy with medication than "poor sleepers."…”
Section: Interventionsmentioning
confidence: 54%
“…This could confirm our observation that the interplay between cognitive performance, sigma activity, and maturation is also dependent on the complexity of the cognitive task. Finally, the inclusion of medication-naïve patients would be desirable since MPH affects sleep behavior [70, 71], and it is unclear whether a discontinuation of MPH for 48 hours is sufficient to adjust for potential withdrawal or rebound effects.…”
Section: Discussionmentioning
confidence: 99%